The neuropathology of experimental chronic manganese poisoning in rats. A preliminary report - Cardozo, José; Bonilla, Ernesto (Investigación Clínica, 2013)
Adult male-Sprague-Dawley rats were exposed to manganese for a period of eight months by giving them drinking water containing 0.1, 1.0 and 5.0 mg Mn/ml, as MnCI2. This experimental animal model for chronic manganese poisoning shares neuropathological features with the human disease such as cortical and striatal alterations. Our results suggest that relatively low concentrations of manganese (1.0 mg/lml) orally ingested are capable of inducing morphological alterations as evidenced by light microscopy studies.